High-fluidity lithium battery single-crystal positive electrode material and preparation method thereof

By controlling the prelithiation process and sintering mode, combined with the use of spraying systems and spheroidizing agents, the problem of poor fluidity of lithium battery single crystal materials is solved, and a lithium battery single crystal positive electrode material with high fluidity and excellent electrochemical properties is prepared.

CN119612610AActive Publication Date: 2025-03-14YIYANG GAOFA SANGRUI NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411777548.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The poor liquidity of existing lithium battery single crystal materials has led to agglomeration and plate bonding problems in manufacturing, transportation, storage and client processing.

Method used

By controlling the prelithiation process, the primary fusion of lithium and the precursor and the control of the particle size of primary particles are achieved. Combined with the sintering mode of quenching and heat, a rotary furnace and spraying system are used to achieve uniform coating of the depolymerized particles, and the particles are spheroidized and grown by spheroidizing agents. Finally, the electrostatic adhesion between particles is eliminated through the electrostatic removal device and the fluidity is improved.

Benefits of technology

The prepared lithium battery single crystal positive electrode material has a spherical or spherical morphology with high roundness, smooth surface, low moisture absorption, low adsorption between particles, small resting angle, and high fluidity, which solves the problems of agglomeration and plate bonding, and improves the efficiency of manufacturing, transportation, storage and client processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612610A_ABST
    Figure CN119612610A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: uniformly mixing a precursor, a lithium salt and a modifier, heating to the temperature T1 of 750-850 DEG C in an oxygen-containing atmosphere, sintering for the time t1 to obtain a pre-lithiation intermediate, transferring the pre-lithiation intermediate into an environment with the temperature T2 of 10 DEG C or below, and quenching for the time t2 to obtain a process sample A; dispersing the process sample A in an environment at a temperature T3, spraying a nodulizing agent, and drying to obtain a process sample B; in an oxygen-containing atmosphere, putting the process sample B into an environment with a temperature T4 of 850-1000 DEG C, carrying out shock heating, calcining and crystallizing for a calcining time of t3, and cooling to obtain a single crystal positive electrode material matrix C; and carrying out post-treatment on the single-crystal positive electrode material matrix C to obtain the high-fluidity lithium battery single-crystal positive electrode material. The invention solves the problem of poor flowability and the problems of manufacturing and use caused by the problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a high-fluidity lithium battery single crystal positive electrode material and a preparation method thereof. Background Art

[0002] With the development of society and the progress of science and technology, high energy density, high safety and long cycle life have become the core demands of lithium batteries. In addition to improving material performance through some modification methods, a major way to take into account the above core demands is single crystalization.

[0003] Advantages of single crystalization: (1) The structure is stable and not prone to microcracks. There are few lattice defects inside the crystal, which is conducive to the transmission of lithium ions. (2) The particles are densely structured, the internal arrangement orientation is consistent, and there are no grain boundaries, which can inhibit side reactions with the electrolyte, thereby improving the cycle performance and safety performance, and the thermal stability is also good. (3) It has a strong ability to resist volume shrinkage and expansion, and has high mechanical strength, tap density and compaction density. (4) It is suitable for high voltage scenarios and can increase the energy density to a certain extent by increasing the voltage.

[0004] Disadvantages of single crystalization: (1) The primary particle size is large and the ion transmission path is longer, so the rate performance is poor; (2) The processing requires higher temperature, more sintering times and longer sintering time, so the manufacturing cost is high; (3) The poor fluidity of the material leads to agglomeration and compaction, affecting the manufacturing, transportation, storage and client processing.

[0005] The poor fluidity of single crystal materials is analyzed: the fluidity of single crystal particles is related to the irregular shape of the particles with sharp points, the small size of the particles, the rough surface, the large specific surface area, and the easy moisture absorption. In addition, the complex relationship between the adhesion, friction, van der Waals force, electrostatic force, etc. between the particles hinders the free flow of particles.

[0006] Based on the above problems in preparation and use, existing solutions mainly include: increasing particle size, changing particle morphology, coating dispersants or flow aids, reducing material moisture, packaging in small packages, reducing packaging vacuum, reducing packaging and storage environment humidity, increasing the frequency of the vibrating screen at the front end of the slurry mixing or manual dispersion, etc. The present invention provides another method for improving the poor fluidity of single crystal materials. Summary of the invention

[0007] The purpose of the invention is to provide a high-fluidity lithium battery single crystal positive electrode material and a preparation method thereof, which solves the problem of poor fluidity of single crystal materials in the prior art.

[0008] The present invention is achieved by providing a method for preparing a high-fluidity lithium battery single crystal positive electrode material, the preparation method comprising the following steps:

[0009] Step 1: Evenly mix the precursor, lithium salt and modifier, heat to a temperature T1 of 750°C to 850°C in an oxygen-containing atmosphere, and sinter for a sintering time of t1 to obtain a pre-lithiation intermediate, and quench the pre-lithiation intermediate in an environment with a temperature T2 of less than 10°C for a quenching time of t2 to obtain process sample A;

[0010] Step 2: Place process sample A in an environment at temperature T3, disperse and spray the spheroidizing agent, and dry to obtain process sample B with the spheroidizing agent evenly coated on the surface;

[0011] Step 3: In an oxygen-containing atmosphere, the process sample B is placed in an environment with a temperature T4 of 850°C to 1000°C for rapid calcination and crystallization. The calcination time is t3, and after cooling, a single crystal positive electrode material matrix C is obtained;

[0012] Step 4: The single crystal positive electrode material substrate C is post-processed to obtain a high-fluidity lithium battery single crystal positive electrode material.

[0013] The present invention controls the conditions of the pre-lithiation process, realizes the primary fusion of lithium and the precursor and controls the particle size of the primary particles, so that part of the lithium is embedded in the crystal cell to realize the growth and disintegration of the primary particles, and part of the lithium is fused with the surface of the primary particles for subsequent secondary growth and recrystallization of the particles; then the high temperature is quenched to a temperature T2 environment, so that the pre-lithiation intermediate agglomerates in a high-temperature expansion state are rapidly contracted at low temperature, and internal stress is generated between the particles to realize the depolymerization of the agglomerates, while retaining the pre-lithiation crystal state; after spraying the spheroidizing agent in the temperature T3 environment, the depolymerized particles are uniformly coated, and then the pre-lithiation intermediates are cooled to a temperature T3 environment. The sudden calcination makes the volume of the primary particle unit cell increase rapidly, so that the lithium embedding space is abundant. At the same time, the residual lithium fused on the surface of the primary particle can be quickly embedded in the crystal lattice, so that the primary particle grows. While growing, under the action of the spheroidizer, the particle grows into a highly spherical state. And because the pre-lithiated lithium salt has been completely decomposed and fused with the single particle, under the isolation of the spheroidizer, the high-temperature lithium salt will not melt and wander in the gaps between the particles. The contact area between the particles is smaller, the adhesion is less, and the material sintered at high temperature will be looser and less compacted. Finally, after post-processing, a high-fluidity lithium battery single crystal positive electrode material is obtained.

[0014] In the present invention, the rapid cooling and rapid heating sintering mode can reduce the side reactions in the crystallization process and make the lattice defects less.

[0015] In the present invention, the purpose of the spheroidizer is to trim the angular morphology of the irregular particle tips into spherical or quasi-spherical particles, so that the material particles are round and smooth and have better fluidity, which is beneficial to further improve the compaction density of the material. At the same time, the uniform coating layer formed by the spheroidizer after re-calcination reduces the moisture adsorption on the surface.

[0016] The single crystal positive electrode material prepared by the present invention has a highly rounded spherical or quasi-spherical morphology, a smooth particle surface, low moisture absorption, low adsorption force between particles, a small repose angle, and high fluidity, which solves the agglomeration and agglomeration problems of single crystal materials and improves the manufacturing, transportation, storage, and client processing links.

[0017] The single crystal positive electrode material prepared by the present invention has high vibration and compaction, stable crystal structure and excellent electrochemical performance, is safe and stable under high voltage, has high specific capacity and long cycle life, and can have the characteristics of high energy density, high safety and long cycle life.

[0018] A further technical solution of the present invention is: in the step 1, the sintering time t1 is 1h to 6h, and the time t2 is 0.5h to 2h; in the step 1, the pre-lithiation intermediate is a partially disintegrated non-spherical agglomerate of primary particles, and the primary particles are small single crystal particles with a diameter of 1.5 to 2.5μm. It is further ensured that the pre-lithiation process realizes the primary fusion of lithium and the precursor and controls the particle size of the primary particles, which is conducive to the secondary growth and crystallization of the subsequent particles.

[0019] A further technical solution of the present invention is: in the step 1, the precursor is at least one of an oxide, a hydroxide, a carbonate, and an organic acid salt, and the precursor contains nickel, cobalt, and zero, one or more of Al, Mn, and Ti; the lithium salt is at least one of an oxide, a hydroxide, a carbonate, a phosphate, a nitrate, and an organic acid salt containing lithium; the modifier is at least one of an oxide, a halide, a carbonate, a hydroxide, a phosphide, a boride, and an organic compound containing an effective element, and the effective element is at least one of Al, Mn, Ti, Zr, Nb, Sr, W, B, Zn, Ta, Tl, Ga, V, Sn, Sb, Mo, Cs, Rb, Ru, In, and Ge.

[0020] A further technical solution of the present invention is that the lithium salt is selected from at least one of lithium hydroxide, lithium oxide, lithium fluoride, lithium carbonate, lithium nitrate and lithium acetate.

[0021] A further technical solution of the present invention is: in the step one, the precursor, lithium salt and modifier are mixed evenly, and the mixture is placed in furnace one for calcination, and furnace one is any one of a box furnace, a roller furnace, a push-plate furnace, a tube furnace and a rotary furnace; in the step three, process sample B is placed in furnace two for calcination and crystallization, and furnace two is any one of a box furnace, a roller furnace and a push-plate furnace; in the steps one and three, the oxygen-containing atmosphere is dry air or a gas with an oxygen concentration not lower than that of air, and the specific oxygen concentration is adjusted according to the material composition.

[0022] In the step one, the target temperature of the pre-lithiation sintering process is 750°C to 850°C, the pre-lithiation sintering time is 1 to 6 hours, and the obtained pre-lithiation intermediate is a partially disintegrated non-spherical agglomerate of primary particles, the primary particle diameter of the agglomerate is 1.5 to 2.5 μm, and the primary particle morphology is small single crystal particles with irregular shapes; in the step one, the quenching temperature is below 10°C, and the quenching method includes one or more of air cooling, external auxiliary liquid cooling, and freezing; the quenching treatment is as follows: the pre-lithiation intermediate in a high temperature state is quickly placed in a refrigerant environment below 10°C for cooling, and the cold treatment time is 0.5 to 2 hours; the process sample A after cooling is in a state of deagglomerated and dispersed primary particles, and the particle size and morphology of the primary particles of the pre-lithiation intermediate are retained.

[0023] A further technical solution of the present invention is: the temperature T3 in the step 2 is -10°C to 200°C; the drying temperature is 100°C to 250°C, and the drying time is 1h to 20h.

[0024] A further technical solution of the present invention is: in the step 2, the spheroidizing agent is at least one of oxides, halides, carbonates, hydroxides, phosphides, borides, or organic compounds containing effective elements; and the effective element is at least one of Mg, Si, Ca, Ba, Fe, Sc, Y, La, Ce, Na, and K.

[0025] A further technical solution of the present invention is: in the step 2, process sample A is put into the rotary kiln for rotation and dispersion, and the volume of the material put into the rotary kiln does not exceed one half of the effective volume of the rotary kiln cavity; the rotation speed of the rotary kiln is adjusted according to actual needs; the superposition angle of the multi-directional spraying system in the rotary kiln covers the effective volume of the rotary kiln cavity, the spraying process can be continuous or intermittent, the nozzle has a self-cleaning function, the spraying medium can be a single medium or a mixed medium among liquid, gas, and solid, and the amount, type and time of the spraying medium are determined by the properties and design amount of the spheroidizer and the uniformity of material mixing in the rotary kiln.

[0026] The spheroidizing agent is brought in by the spraying medium of the spraying system; if the spheroidizing agent is an insoluble solid, its particle size must be less than 100 nm; the function of the spheroidizing agent is to spheroidize the primary particles during the calcination process in step three.

[0027] In the step 2, process sample B is in a dispersed primary particle state, retaining the particle size and morphology of the primary particles of process sample A, and the surface of the primary particles is coated with a uniform coating, and the morphology of the coating is determined by the properties of the spheroidizing agent.

[0028] A further technical solution of the present invention is: in the step three, the calcination crystallization time t3 is 2h to 24h. In the step three, the target temperature 2 is 850℃ to 1000℃, and the calcination crystallization time is 2h to 24h; entering the target temperature zone is a sudden heating process without a temperature rise buffer section; the obtained single crystal positive electrode material matrix C single particle has a highly rounded spherical or quasi-spherical single crystal morphology, a smooth surface or a fully covered uniform coating film, and the single particle size is 2.0 to 4.5μm.

[0029] A further technical solution of the present invention is: the post-processing step in step 4 includes: the single crystal positive electrode material matrix C is crushed, gas-powdered, batch-mixed, screened, demagnetized and then destaticized to obtain the single crystal positive electrode material matrix C.

[0030] A further technical solution of the present invention is: in the step 4, the crushing and gas powder parameters are adjusted according to the state of the substrate C; the secondary coating sintering or not is determined by the material type and the use method, and whether to coat is determined according to the use of the material; if secondary coating sintering is required, the coating agent used for coating can be at least one of the oxides, carbonates, hydroxides, phosphides, borides, halides or organic compounds containing at least one element among Al, Mg, K, Ti, Nb, W, B, Mo, Si, Ca, Ba, C, and Fe, and the coating agent can be in any state of liquid and / or solid and / or gas. The coating method is determined by the state of the coating agent. If it contains or not, When it is a soluble solid, its particle size must be less than 100nm, and some substances in the coating agent can also act as an anti-caking agent; if secondary coating and sintering are required, the sintering kiln can be any one of a box furnace, a roller furnace, a push plate furnace, a tube furnace, and a rotary furnace. The sintering atmosphere is divided into an oxygen-containing atmosphere and an oxygen-free atmosphere. The sintering temperature is 150℃~750℃, the sintering time is 1h~20h, and the pulverization method after sintering can be mechanical crushing and / or sieving through a sieve; the pre-finished product D has a spherical or quasi-spherical single crystal morphology with high roundness, which can be a single particle or a single particle aggregate of less than 10 particles, with a smooth surface, low moisture absorption, a repose angle of less than 40°, and a particle size D50 of 2.0~6.5μm.

[0031] The purpose of the material of the present invention being subjected to a static electricity removal device before packaging is to eliminate the static electricity adhesion caused by the collision and friction between particles during the crushing, gas powder, batch mixing, screening and other processes, improve the fluidity of the material, and reduce the soft agglomeration of the packaged material during storage and transportation. The static electricity removal device can be an ion eliminator or a high-voltage generator; the single crystal positive electrode material product E obtained after static electricity removal is the high-fluidity lithium battery single crystal positive electrode material of the present invention, with an angle of repose less than 40° and a particle size D50 of 2.0 to 6.5 μm.

[0032] A further technical solution of the present invention is: the post-processing step in step four includes: the single crystal positive electrode material matrix C is crushed and gas-powdered, and then subjected to secondary coating sintering, batch mixing, screening, demagnetization and then static electricity removal to obtain the single crystal positive electrode material matrix C.

[0033] A further technical solution of the present invention is: the coating agent for the secondary coating is at least one of oxides, carbonates, hydroxides, phosphides, borides, halides, and organic compounds containing effective elements, the effective elements are at least one of Al, Mg, K, Ti, Nb, W, B, Mo, Si, Ca, Ba, C, and Fe, the secondary sintering temperature is 150°C to 750°C, and the sintering time is 1h to 20h.

[0034] In the present invention, the sudden cooling is to directly reach the target temperature without going through a temperature-lowering process; the sudden heating is to directly reach the target temperature without going through a temperature-raising process.

[0035] The present invention also provides a high-fluidity lithium battery single crystal positive electrode material, which is obtained by the preparation method of the present invention. The chemical formula of the positive electrode material is: Li 1+n Ni x Co y M z A m O 2+w , wherein, -0.5≤n≤0.5, 0.2≤x<1, 0≤y≤0.4, 0≤z≤2, 0≤m≤0.01, -0.5≤w≤2; M is zero, one or more of Al, Mn, and Ti; A is zero, one or more of Al, Mn, Mg, Ti, Fe, Zr, Y, Ca, Nb, Sr, Sc, W, B, Ba, Zn, Ce, Ta, Tl, Ga, La, V, Sn, Sb, Si, Mo, Cs, Rb, Ru, In, Ge, K, Na, C, H, F, Cl, and P; the repose angle of the high-fluidity lithium battery single crystal positive electrode material is less than 40°, and the particle size D50 is 2.0 to 6.5 μm.

[0036] A further technical solution of the present invention is: the molar number of the effective element of the modifier conforms to the range of m in the chemical formula of the present invention, and the m range of the modifier is 0.0005-0.005; the molar number of the effective element of the spheroidizer conforms to the range of m in the chemical formula of the present invention, and the m range of the spheroidizer is 0.0005-0.005; the molar number of the effective element of the coating agent conforms to the range of m in the chemical formula of the present invention, and the m range of the coating agent is preferably 0.0005-0.004, the molar number of the lithium element of the lithium source conforms to the range of 1+n in the chemical formula of the present invention, and the molar number of the lithium element is in the range of 0.5-1.5, the molar number of the effective element of the precursor conforms to the range of x, y, and z in the chemical formula of the present invention, and the molar number of the effective element of the precursor is in the range of 0.2-3.4.

[0037] Beneficial effects of the present invention: 1. The present invention provides a method for preparing a high-fluidity lithium battery single crystal positive electrode material, which solves the problem of poor fluidity of single crystal materials in the prior art and the manufacturing and use problems caused by this problem, and improves the material performance by modification means. The high-fluidity lithium battery single crystal positive electrode material includes a spherical or quasi-spherical morphology with high roundness, a smooth surface of single particles, low moisture absorption, low adsorption force between particles, a small repose angle, and high fluidity, which solves the agglomeration and agglomeration problems of single crystal materials and improves the manufacturing, transportation, storage, and client processing links;

[0038] 2. The present invention controls the pre-lithiation process to achieve primary fusion of lithium and precursor, controls the particle size of primary particles, achieves particle deagglomeration through high-temperature quenching, uses a rotary kiln and a customized spraying system to achieve uniform coating of deagglomerated particles, performs sudden calcination again to achieve primary particle spheroidization growth, and finally eliminates the electrostatic adhesion between particles through a customized static electricity removal device to obtain a high-fluidity lithium battery single crystal positive electrode material; the purpose of the pre-lithiation of the present invention is to embed part of the lithium into the unit cell to achieve the growth and disintegration of primary particles, and part of the lithium fuses with the surface of the primary particles for subsequent secondary growth and recrystallization of the particles; the purpose of the quenching treatment of the present invention is to make the pre-lithiation intermediate agglomerates in a high-temperature expansion state shrink rapidly at low temperature, generate internal stress between the particles, so as to achieve deagglomeration of the agglomerates, while retaining the crystalline state of pre-lithiation.

[0039] 3. The present invention adopts a calcination and spraying system in order to make the primary particles evenly coated with the spheroidizing agent and realize continuous operation in the production line, thereby reducing the production breakpoint process; the purpose of the spheroidizing agent is to trim the angular morphology of the irregular particle tips into spherical or quasi-spherical particles, so that the material particles are round and smooth and have better fluidity, which is conducive to further improving the compaction density of the material. At the same time, the uniform coating layer formed by the spheroidizing agent after re-calcination reduces the surface moisture adsorption.

[0040] 4. The purpose of the present invention's re-sudden calcination without a heating process and directly entering the target temperature T4 is to quickly increase the temperature so that the volume of the primary particle unit cell quickly increases, the lithium embedding space is abundant, and the residual lithium fused on the surface of the primary particle can be quickly embedded in the lattice to make the primary particle grow. While growing, under the action of the spheroidizer, the particles grow into a highly spherical state. Moreover, since the pre-lithiated lithium salt has been completely decomposed and fused with the single particle, under the isolation of the spheroidizer, the high-temperature lithium salt will not melt and wander in the gaps between the particles. The contact area between the particles is smaller, the adhesion is less, and the material sintered at high temperature will be looser and less compacted. In addition, the sudden cooling and heating sintering mode can reduce side reactions in the crystallization process and reduce lattice defects.

[0041] 5. The purpose of the material of the present invention being subjected to a static electricity removal device before packaging is to eliminate the static electricity adhesion caused by the collision and friction between particles during the processes of crushing, gas powder, batch mixing, screening, etc., to improve the fluidity of the material and reduce the soft agglomeration of the packaged material during storage and transportation.

[0042] 6. The single crystal positive electrode material prepared by the present invention has high vibration and compaction, stable crystal structure and excellent electrochemical properties, is safe and stable under high voltage, has high specific capacity and long cycle life, and can have the characteristics of high energy density, high safety and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 XRD diagrams of the single crystal positive electrode material obtained in Example 1 and the comparative example material;

[0044] Figure 2 This is a SEM image of the pre-lithiation intermediate obtained in Example 1 at a magnification of 1000 times;

[0045] Figure 3 This is a SEM image of process sample A obtained in Example 1 at a magnification of 1000 times;

[0046] Figure 4 This is a SEM image of the substrate C obtained in Example 1 at a magnification of 1000 times;

[0047] Figure 5 This is a SEM image of the finished product sample E obtained in Example 1 at a magnification of 10000 times;

[0048] Figure 6 This is a SEM image of the single crystal positive electrode material obtained in the comparative example at a magnification of 10,000 times;

[0049] Figure 7 The first charge and discharge curves of the 2032 button-type batteries made of the single crystal positive electrode material obtained in Example 1 and the single crystal positive electrode material of the comparative example respectively, with a current density of 0.2C and a voltage of 3.0V to 4.5V at room temperature;

[0050] Figure 8 The charge-discharge cycle curves of 2032 button-type batteries made of the single crystal positive electrode material obtained in Example 1 and the single crystal positive electrode material of the comparative example at room temperature with a current density of 1C and a voltage of 3.0V to 4.5V. DETAILED DESCRIPTION

[0051] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0052] As used herein:

[0053] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0054] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0055] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. Preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing the specific embodiments and are not intended to limit the present invention. In the embodiments, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0057] The present invention provides a method for preparing a high-fluidity lithium battery single crystal positive electrode material, the preparation method comprising the following steps:

[0058] Step 1: Evenly mix the precursor, lithium salt and modifier, heat to a temperature T1 of 750°C to 850°C in an oxygen-containing atmosphere, and sinter for a sintering time of t1 to obtain a pre-lithiation intermediate, and quench the pre-lithiation intermediate in an environment with a temperature T2 of less than 10°C for a quenching time of t2 to obtain process sample A;

[0059] In the step 1, the sintering time t1 is 1 h to 6 h, and the time t2 is 0.5 h to 2 h; the pre-lithiation intermediate in the step 1 is a partially disintegrated non-spherical agglomerate of primary particles, and the primary particles are small single crystal particles with a diameter of 1.5 to 2.5 μm.

[0060] In the step 1, the precursor is at least one of oxides, hydroxides, carbonates, and organic acid salts, and the precursor contains nickel, cobalt, and zero, one, or more of Al, Mn, and Ti; the lithium salt is at least one of lithium-containing oxides, hydroxides, carbonates, phosphates, nitrates, and organic acid salts; the modifier is at least one of oxides, halides, carbonates, hydroxides, phosphides, borides, and organic compounds containing effective elements, and the effective elements are at least one of Al, Mn, Ti, Zr, Nb, Sr, W, B, Zn, Ta, Tl, Ga, V, Sn, Sb, Mo, Cs, Rb, Ru, In, and Ge. The lithium salt is selected from at least one of lithium hydroxide, lithium oxide, lithium fluoride, lithium carbonate, lithium nitrate, and lithium acetate.

[0061] In the step one, the precursor, lithium salt and modifier are mixed evenly, and the mixture is placed in furnace one for calcination. Furnace one is any one of a box furnace, a roller furnace, a push-plate furnace, a tube furnace and a rotary furnace; in the step three, process sample B is placed in furnace two for calcination and crystallization. Furnace two is any one of a box furnace, a roller furnace and a push-plate furnace; in the steps one and three, the oxygen-containing atmosphere is dry air or a gas with an oxygen concentration not lower than that of air, and the specific oxygen concentration is adjusted according to the material composition.

[0062] Step 2: Place process sample A in an environment at temperature T3, disperse and spray the spheroidizing agent, and dry to obtain process sample B with the spheroidizing agent evenly coated on the surface;

[0063] The temperature T3 in step 2 is -10°C to 200°C; the drying temperature is 100°C to 250°C, and the drying time is 1h to 20h.

[0064] In the step 2, process sample A is put into the rotary kiln and dispersed by rotation, and the volume of the material put into the rotary kiln does not exceed one half of the effective volume of the rotary kiln cavity; the rotation speed of the rotary kiln is adjusted according to actual needs; the superposition angle of the multi-directional spraying system in the rotary kiln covers the effective volume of the rotary kiln cavity, the spraying process can be continuous or intermittent, the nozzle has a self-cleaning function, the spraying medium can be a single medium or a mixed medium among liquid, gas, and solid, and the amount and type of the spraying medium and the time of the spraying process are determined by the properties and design amount of the spheroidizer and the uniformity of material mixing in the rotary kiln.

[0065] In the step 2, the spheroidizing agent is at least one of oxides, halides, carbonates, hydroxides, phosphides, borides, or organic compounds containing effective elements; the effective elements are at least one of Mg, Si, Ca, Ba, Fe, Sc, Y, La, Ce, Na, and K.

[0066] The spheroidizing agent is brought in by the spraying medium of the spraying system; if the spheroidizing agent is an insoluble solid, its particle size must be less than 100 nm; the function of the spheroidizing agent is to spheroidize the primary particles during the calcination process in step three.

[0067] In the step 2, process sample B is in a dispersed primary particle state, retaining the particle size and morphology of the primary particles of process sample A, and the surface of the primary particles is coated with a uniform coating, and the morphology of the coating is determined by the properties of the spheroidizing agent.

[0068] Step 3: In an oxygen-containing atmosphere, the process sample B is placed in an environment with a temperature T4 of 850°C to 1000°C for rapid calcination and crystallization. The calcination time is t3, and after cooling, a single crystal positive electrode material matrix C is obtained;

[0069] In the step 3, the calcination crystallization time t3 is 2h to 24h. In the step 3, the target temperature 2 is 850℃ to 1000℃, and the calcination crystallization time is 2h to 24h; entering the target temperature zone is a sudden heating process without a temperature rise buffer section; the obtained single crystal positive electrode material matrix C single particle has a highly rounded spherical or quasi-spherical single crystal morphology, a smooth surface or a fully covered uniform coating film, and the single particle size is 2.0 to 4.5μm.

[0070] Step 4: The single crystal positive electrode material substrate C is post-processed to obtain a high-fluidity lithium battery single crystal positive electrode material.

[0071] The post-processing steps in step four include: the post-processing steps in step four include: the single crystal positive electrode material matrix C is crushed and gas-powdered, and then subjected to secondary coating and sintering or not, and then batch mixed, screened, demagnetized and then destaticized to obtain the single crystal positive electrode material matrix C.

[0072] The coating agent for the secondary coating is at least one of oxides, carbonates, hydroxides, phosphides, borides, halides and organic compounds containing effective elements, and the effective elements are at least one of Al, Mg, K, Ti, Nb, W, B, Mo, Si, Ca, Ba, C and Fe. The secondary sintering temperature is 150°C to 750°C, and the sintering time is 1h to 20h.

[0073] In the step 4, the crushing and gas powder parameters are adjusted according to the state of the matrix C; the secondary coating sintering or not is determined by the material type and the use method, and whether to coat is determined according to the use of the material; if secondary coating sintering is required, the coating agent used for coating can be at least one of the oxides, carbonates, hydroxides, phosphides, borides, halides or organic compounds containing at least one element among Al, Mg, K, Ti, Nb, W, B, Mo, Si, Ca, Ba, C, and Fe. The coating agent can be any state of liquid and / or solid and / or gas. The coating method is determined by the state of the coating agent. If it contains insoluble solids, Its particle size needs to be less than 100nm, and some substances in the coating agent can also act as anti-caking agents; if secondary coating sintering is required, the sintering kiln can be any one of a box furnace, a roller furnace, a push plate furnace, a tube furnace, and a rotary furnace. The sintering atmosphere is divided into an oxygen-containing atmosphere and an oxygen-free atmosphere. The sintering temperature is 150°C to 750°C, and the sintering time is 1h to 20h. The pulverization method after sintering can be mechanical crushing and / or sieving through a sieve; the pre-finished product D has a highly rounded spherical or quasi-spherical single crystal morphology, which can be a single particle or a single particle aggregate of less than 10 particles, with a smooth surface, low moisture absorption, a repose angle of less than 40°, and a particle size D50 of 2.0 to 6.5μm.

[0074] A high-fluidity lithium battery single crystal positive electrode material is prepared by the above method. The chemical formula of the positive electrode material is: Li 1+n Ni x Co y M z A m O 2+w , wherein, -0.5≤n≤0.5, 0.2≤x<1, 0≤y≤0.4, 0≤z≤2, 0≤m≤0.01, -0.5≤w≤2; M is zero, one or more of Al, Mn, and Ti; A is zero, one or more of Al, Mn, Mg, Ti, Fe, Zr, Y, Ca, Nb, Sr, Sc, W, B, Ba, Zn, Ce, Ta, Tl, Ga, La, V, Sn, Sb, Si, Mo, Cs, Rb, Ru, In, Ge, K, Na, C, H, F, Cl, and P; the repose angle of the high-fluidity lithium battery single crystal positive electrode material is less than 40°, and the particle size D50 is 2.0 to 6.5 μm.

[0075] The molar number of the effective element of the modifier conforms to the range of m in the chemical formula of the present invention, and the range of m of the modifier is 0.0005-0.005; the molar number of the effective element of the spheroidizer conforms to the range of m in the chemical formula of the present invention, and the range of m of the spheroidizer is 0.0005-0.005; the molar number of the effective element of the coating agent conforms to the range of m in the chemical formula of the present invention, and the range of m of the coating agent is preferably 0.0005-0.004; the molar number of the lithium element of the lithium salt in the positive electrode material is 0.5-1.5, and the molar number of the effective element of the precursor is 0.2-3.4.

[0076] The specific implementation methods are as follows:

[0077] Example 1

[0078] The steps for preparing the single crystal positive electrode material of this embodiment are as follows:

[0079] Step 1: Weigh Li2CO3 and Ni in a molar ratio of 1.07:1 0.5 Co 0.2 Mn 0.3 (OH)2 and Ta2O5 (wherein Ta accounts for 2000ppm by mass) are doped and placed together in a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min to obtain a high-mix material; the high-mix material is placed in a sagger and placed in a roller furnace, and after gradient heating to reach the target temperature zone, it is sintered at 800℃ for 6h, and air is introduced into the furnace during the sintering process. After the sintering time is over, a pre-lithiation intermediate is obtained, and then the high-temperature pre-lithiation intermediate is rapidly transferred to an incubator assisted by liquid nitrogen for quenching. The temperature in the incubator is -10℃, and the cooling is completed after insulation for 1 hour to obtain a cooled process sample A;

[0080] Step 2: Process sample A is fed into a rotary kiln at room temperature through a weighing system via a cooling device discharge port. The rotary kiln is rotated at a speed of 10 r / min for 15 min until the material is evenly dispersed. The rotary kiln is then continuously rotated and a multi-directional spraying system is provided in the rotary kiln to spray a certain amount of cerium acetate (Ce mass ratio 2000 ppm) using ethanol as a medium into the kiln. The spraying is intermittent and lasts for 1 h. After the spraying is completed, the rotary kiln is continuously rotated for 30 min to mix the mixture evenly. The exhaust port of the rotary kiln is opened and the temperature of the rotary kiln is raised to 120°C. The mixture is dried for 2 h to obtain process sample B having a surface evenly coated with cerium acetate.

[0081] Step 3: Process sample B is transferred to the weighing system through the unloading port of the rotary kiln, and the unloading bowl is put into the roller furnace. Under the air atmosphere, it directly enters the target temperature zone at 950°C for 6 hours to calcine and crystallize, and finally cools down in the furnace cooling zone and takes out of the furnace to obtain the single crystal positive electrode material matrix C;

[0082] Step 4: After the single crystal cathode material matrix C is crushed and gas-powdered, it is coated with Al2O3 (Al mass accounts for 6000ppm) for the second time, and the mixed material is coated with a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min. The dry package is put into a bowl and put into a roller furnace. In an air atmosphere, it reaches the target temperature zone through a gradient heating temperature zone and is sintered at 600℃ for 6h. Finally, it is cooled down in the furnace cooling zone and taken out of the furnace to obtain a pre-finished product D;

[0083] After the pre-finished product D enters the packaging system, it is batch mixed, screened, and demagnetized, and then enters the anti-static device. The material after anti-static treatment is the single crystal positive electrode material finished product E, which is then unloaded through the weighing system and enters the packaging bag for sealing and packaging.

[0084] Example 2

[0085] The steps for preparing the single crystal positive electrode material of this embodiment are as follows:

[0086] Step 1: Weigh Li2CO3 and Ni in a molar ratio of 1.06:1 0.6 Co 0.1 Mn 0.3 (OH)2 and ZrO2 (wherein the mass proportion of Zr is 4000ppm) are added and placed together in a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min to obtain a high-mix material; the high-mix material is placed in a sagger and placed in a roller furnace, and after the temperature reaches the target temperature zone through gradient heating, it is sintered at 790℃ for 6h, and air is introduced into the furnace during the sintering process. After the sintering time is over, a pre-lithiation intermediate is obtained, and then the high-temperature pre-lithiation intermediate is rapidly transferred to an incubator assisted by liquid nitrogen for rapid cooling. The temperature in the incubator is -10℃, and the cooling is completed after 1 hour of insulation to obtain a cooled process sample A;

[0087] Step 2: Process sample A is fed into a rotary kiln at room temperature through a weighing system via a cooling device discharge port. The rotary kiln is rotated at a speed of 10 r / min for 15 min until the material is evenly dispersed. The rotary kiln is then continuously rotated and a quantitative amount of LaCl3 (La mass percentage 1000 ppm) with ethanol as a medium is sprayed into the furnace through a multi-directional spraying system customized for the rotary kiln. The spraying is intermittent and lasts for 1 h. After the spraying is completed, the rotary kiln is continuously rotated for 30 min to mix the mixture evenly. The rotary kiln exhaust port is opened and the temperature of the rotary kiln is raised to 120°C. The mixture is dried for 2 h to obtain a process sample B with a surface evenly coated with LaCl3.

[0088] Step 3: Process sample B is transferred to the weighing system through the rotary kiln discharge port, and the sample is discharged into the roller furnace. In the air atmosphere, it is directly placed in the target temperature zone at 900°C for 8 hours of calcination and crystallization, and finally cooled down in the furnace cooling zone and discharged from the furnace to obtain the single crystal positive electrode material matrix C;

[0089] Step 4: After the single crystal cathode material matrix C is crushed and gas-powdered, it is coated with Al2O3 (Al mass accounts for 3000ppm) for the second time, and the mixed material is coated with a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min. The dry package is put into a bowl and put into a roller furnace. In an air atmosphere, it reaches the target temperature zone through the gradient heating temperature zone and is sintered at 600℃ for 6h. Finally, it is cooled down in the furnace cooling zone and taken out of the furnace to obtain a pre-finished product D;

[0090] After the pre-finished product D enters the packaging system, it is batch mixed, screened, and demagnetized, and then enters the customized anti-static device. The material after anti-static treatment is the single crystal positive electrode material finished product E, which is then unloaded through the weighing system and enters the packaging bag for sealing and packaging.

[0091] Example 3

[0092] The steps for preparing the single crystal positive electrode material of this embodiment are as follows:

[0093] Step 1: Weigh LiOH·H2O and Ni in a molar ratio of 1.05:1 0.7 Co 0.1 Mn 0.2 (OH)2 and doped with ZrO2 (wherein the mass proportion of Zr is 3000ppm) are placed together in a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min to obtain a high-mix material; the high-mix material is placed in a sagger and placed in a roller furnace, and after the temperature reaches the target temperature zone through gradient heating, it is sintered at 790°C for 4h, and oxygen (oxygen concentration is 90% and above) is introduced into the furnace during the sintering process. A pre-lithiation intermediate is obtained after the sintering time is completed, and then the high-temperature pre-lithiation intermediate is rapidly transferred to a freezing-assisted cooling incubator for quenching. The temperature in the incubator is -5°C, and the cooling is completed after 1 hour of insulation to obtain a cooled process sample A;

[0094] Step 2: Process sample A is fed into a rotary kiln at room temperature through a cooling device discharge port and a weighing system. The rotary kiln is rotated at a speed of 10r / min for 15min until the material is evenly dispersed. Then the rotary kiln is continuously rotated and a quantitative amount of BaCl2 (Ba mass ratio is 1500ppm) with propanol as a medium is sprayed into the furnace through a multi-directional spraying system customized for the rotary kiln. The spraying is intermittent and lasts for 1h. After the spraying is completed, the rotary kiln is continuously rotated for 40min to mix the batches evenly. The exhaust port of the rotary kiln is opened and the temperature of the rotary kiln is raised to 150°C. The rotary kiln is dried for 5h to obtain a process sample B with a surface uniformly coated with BaCl2.

[0095] Step 3: Process sample B is transferred to the weighing system through the unloading port of the rotary kiln, and the unloading bowl is placed in the roller furnace. Under the oxygen atmosphere (oxygen concentration is 90% or above), it is directly placed in the target temperature zone at 870°C for 10 hours for calcination and crystallization, and finally cooled down in the furnace cooling zone and discharged from the furnace to obtain the single crystal positive electrode material matrix C;

[0096] Step 4: After the single crystal cathode material matrix C is crushed and gas-powdered, it is coated with B2O3 (B mass accounts for 1000ppm) for the second time, and the mixture is coated with a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min, and the dry package is put into a bowl and put into a roller furnace. In an oxygen atmosphere (oxygen concentration is 90% or above), after reaching the target temperature zone through the gradient temperature rising zone, it is sintered at 500℃ for 6h, and finally cooled down with the furnace in the furnace cooling zone to obtain a pre-finished product D;

[0097] After the pre-finished product D enters the packaging system, it is batch mixed, screened, and demagnetized, and then enters the customized anti-static device. The material after anti-static treatment is the single crystal positive electrode material finished product E, which is then unloaded through the weighing system and enters the packaging bag for sealing and packaging.

[0098] Example 4

[0099] The steps for preparing the single crystal positive electrode material of this embodiment are as follows:

[0100] Step 1: Weigh LiOH·H2O and Ni in a molar ratio of 1.04:1 0.8 Co 0.1 Mn 0.1 (OH)2 and doped with ZrO2 (wherein the mass proportion of Zr is 2000ppm) are placed together in a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min to obtain a high-mix material; the high-mix material is placed in a sagger and placed in a roller furnace, and after the temperature reaches the target temperature zone through gradient heating, it is sintered at 780°C for 4h, and oxygen (oxygen concentration is 95% and above) is introduced into the furnace during the sintering process. A pre-lithiation intermediate is obtained after the sintering time is completed, and then the high-temperature pre-lithiation intermediate is rapidly transferred to a freezing-assisted cooling incubator for quenching. The temperature in the incubator is -5°C, and the cooling is completed after 1 hour of insulation to obtain a cooled process sample A;

[0101] Step 2: Process sample A is fed into a rotary kiln at room temperature through a weighing system via a cooling device discharge port. The rotary kiln is rotated at a speed of 10 r / min for 15 min until the material is evenly dispersed. The rotary kiln is then continuously rotated and a quantitative amount of tetrabutyl silicate (1000 ppm by mass of Si) with pure water as the medium is sprayed into the furnace through a multi-directional spraying system customized for the rotary kiln. The spraying is intermittent and lasts for 1 h. After the spraying is completed, the rotary kiln is continuously rotated for 40 min to mix the mixture evenly. The rotary kiln exhaust port is opened and the temperature of the rotary kiln is raised to 180 ° C. The mixture is dried for 5 h to obtain a process sample B with a surface uniformly coated with SiO2.

[0102] Step 3: Process sample B is transferred to the weighing system through the unloading port of the rotary kiln, and the unloading bowl is placed in the roller furnace. Under the oxygen atmosphere (oxygen concentration is 95% or above), it is directly placed in the target temperature zone at 850°C for 10 hours for calcination and crystallization, and finally cooled down in the furnace cooling zone and discharged from the furnace to obtain the single crystal positive electrode material matrix C;

[0103] Step 4: After the single crystal cathode material matrix C is crushed and gas-powdered, it is coated with B2O3 (B mass accounts for 1500ppm) for the second time, and the mixed material is coated with a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min, and the dry package is put into a bowl and put into a roller furnace. In an oxygen atmosphere (oxygen concentration is 95% or above), after reaching the target temperature zone through the gradient temperature rising temperature zone, it is sintered at 500℃ for 6h, and finally cooled down with the furnace in the furnace cooling zone to obtain a pre-finished product D;

[0104] After the pre-finished product D enters the packaging system, it is batch mixed, screened, and demagnetized, and then enters the customized anti-static device. The material after anti-static treatment is the single crystal positive electrode material finished product E, which is then unloaded through the weighing system and enters the packaging bag for sealing and packaging.

[0105] Example 5

[0106] The steps for preparing the single crystal positive electrode material of this embodiment are as follows:

[0107] Step 1: Weigh LiOH·H2O and Ni in a molar ratio of 1.05:1 0.8 Mn 0.2 (OH)2 and Nb2O5 (wherein Nb accounts for 3000ppm by mass) are doped together and placed in a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min to obtain a high-mix material; the high-mix material is placed in a sagger and placed in a roller furnace, and after the temperature reaches the target temperature zone through gradient heating, it is sintered at 800℃ for 4h, and oxygen (oxygen concentration is 95% and above) is introduced into the furnace during the sintering process. A pre-lithiation intermediate is obtained after the sintering time is completed, and then the high-temperature pre-lithiation intermediate is rapidly transferred to a freezing-assisted cooling incubator for quenching. The temperature in the incubator is -5℃, and the cooling is completed after insulation for 1 hour to obtain a cooled process sample A;

[0108] Step 2: Process sample A is fed into a rotary kiln at room temperature through a cooling device discharge port and a weighing system. The rotary kiln is rotated at a speed of 10 r / min for 15 min until the material is evenly dispersed. Then the rotary kiln is continuously rotated and a certain amount of Ca(OH)2 (Ca mass percentage 5000 ppm) with ethanol as a medium is sprayed into the furnace through a multi-directional spraying system customized for the rotary kiln. The spraying is intermittent and lasts for 1 h. After the spraying is completed, the rotary kiln is continuously rotated for 50 min to mix the mixture evenly. The exhaust port of the rotary kiln is opened and the temperature of the rotary kiln is raised to 180°C. The mixture is dried for 6 h to obtain process sample B with a surface evenly coated with CaO.

[0109] Step 3: Process sample B is transferred to the weighing system through the unloading port of the rotary kiln, and the unloading bowl is placed in the roller furnace. Under the oxygen atmosphere (oxygen concentration is 95% or above), it is directly placed in the target temperature zone at 880°C for 10 hours for calcination and crystallization, and finally cooled down in the furnace cooling zone and discharged from the furnace to obtain the single crystal positive electrode material matrix C;

[0110] Step 4: After the single crystal cathode material matrix C is crushed and gas-powdered, it is coated with Al2O3 (Al mass accounts for 2000ppm) for the second time, and the mixed material is coated with a high-efficiency mixer, and mixed at a high speed of 300r / min for 30min. The dry package is put into a bowl and put into a roller furnace. In an oxygen atmosphere (oxygen concentration is 95% or above), it reaches the target temperature zone through the gradient temperature rising zone and is sintered at 600℃ for 6h. Finally, it is cooled down with the furnace in the furnace cooling zone and taken out of the furnace to obtain a pre-finished product D;

[0111] After the pre-finished product D enters the packaging system, it is batch mixed, screened, and demagnetized, and then enters the customized anti-static device. The material after anti-static treatment is the single crystal positive electrode material finished product E, which is then unloaded through the weighing system and enters the packaging bag for sealing and packaging.

[0112] Comparative Example

[0113] The commercially available conventional NCM523 single crystal positive electrode material was used as a control.

[0114] test:

[0115] 1) XRD test was performed on the single crystal positive electrode material obtained in Example 1. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that there is no significant difference in the peak position and peak intensity of the two groups of curves in Example 1 compared with the comparative example. The peak intensity ratio of the two groups of peaks (003) and (104) in the curve of Example 1 is ≥1.2, indicating that the degree of mixing of lithium and nickel in the positive electrode material is low; the two groups of peaks (006 / 012) and (018 / 110) are obviously split, indicating that the positive electrode material has a good layered structure and a high degree of crystallinity, and the synthetic sample has high purity and no impurity phase.

[0116] 2) The single crystal positive electrode material prepared in Example 1 was tested by scanning electron microscope (SEM), and the results were as follows: Figures 2 to 5 .from Figure 2 It can be seen that the pre-lithiation intermediate prepared in Example 1 is a partially disintegrated non-spherical agglomerate of primary particles. Figure 3 It can be seen that the process sample A prepared in Example 1 is in a state of depolymerized and dispersed primary particles, retaining the particle size and morphology of the primary particles of the pre-lithiation intermediate; Figure 4 It can be seen that the matrix C prepared in Example 1 is a single particle with a spherical or quasi-spherical single crystal morphology with high roundness; Figure 5 It can be seen that the finished product sample E obtained in Example 1 is a single particle or aggregate with a spherical or quasi-spherical single crystal morphology with a high roundness, and the surface has a smooth full-covering coating layer; Figure 6 It can be seen that the material of the comparative example has an irregular polygonal morphology with sharp angular contact points.

[0117] 3) The electrochemical performance of the single crystal positive electrode materials prepared in Examples 1-5 and the single crystal positive electrode materials of the comparative example was tested. The results are as follows: Figure 7 , Figure 8 As shown in Table 1. Figure 7 The first charge and discharge curves of the 2032 button-type batteries made of the single crystal positive electrode material obtained in Example 1 and the single crystal positive electrode material of the comparative example are shown in Figure 1, respectively, with a current density of 0.2C and a voltage of 3.0V to 4.5V at room temperature. Figure 8 The following are the charge-discharge cycle curves of the 2032 button-type battery made of the single crystal positive electrode material obtained in Example 1 and the single crystal positive electrode material of the comparative example at room temperature, current density 1C, voltage 3.0V-4.5V. The electrochemical performance test method is as follows: the single crystal positive electrode material obtained in Example 1 or the single crystal positive electrode material of the comparative example is mixed evenly with acetylene black and polyvinylidene fluoride (PVDF) in a proper amount of N-methylpyrrolidone (NMP) solution in a mass ratio of 8:1:1, and then coated on aluminum foil to make a positive electrode sheet; the negative electrode sheet is a lithium sheet, and a diaphragm and an electrolyte are added, wherein the electrolyte is a 1 mol / L LiPF6 solution, the solvent is a mixed solution of EC, DEC and DMC, and the volume ratio of EC, DEC and DMC is 1:1:1, and the button-type battery of model 2032 is assembled in a glove box filled with argon. The test was conducted on a LAND battery tester with current densities of 0.2C and 1.0C, a test voltage range of 3.0V to 4.5V, and a test temperature of room temperature 25°C.

[0118] 4) The single crystal positive electrode materials prepared in Examples 1-5 and the single crystal positive electrode materials of the comparative example were tested for repose angle and fluidity. The results are shown in Table 2.

[0119] 5) The single crystal positive electrode materials prepared in Examples 1-5 and the single crystal positive electrode materials of the comparative example were subjected to moisture absorption tests. The results are shown in Table 3.

[0120] Table 1 Electrochemical performance test results

[0121]

[0122] from Figure 7 As can be seen from Table 1, the first discharge capacity of the single crystal positive electrode material prepared in Example 1 is higher than that of the comparative example material, and the first efficiency is also higher; Figure 8It can be seen that the cycle retention rate of the single crystal positive electrode material prepared in Example 1 is also higher than that of the comparative example material. It can be seen that the single crystal positive electrode material prepared by the present invention has better electrochemical performance and better cycle life.

[0123] Table 2 Test results of angle of repose and Carr's fluidity index

[0124]

[0125] As can be seen from Table 2, compared with the comparative material, the single crystal positive electrode material prepared in Examples 1-5 has a lower repose angle and a higher Carr's fluidity index, indicating that its fluidity is higher. Comparing the initial state and the state after three months of storage, the comparative material has undergone obvious agglomeration and agglomeration, while the repose angle and flow index of the single crystal positive electrode material prepared in Examples 1-5 have only slight changes, indicating that the adsorption is low and the fluidity is not affected by storage.

[0126] Table 3 Moisture absorption value test results

[0127]

[0128] It can be seen from Table 3 that compared with the comparative example materials, the single crystal positive electrode materials prepared in Examples 1-5 have lower moisture absorption values, indicating that the moisture adsorption on their surfaces is slower.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-fluidity lithium battery single crystal positive electrode material, characterized in that: The preparation method comprises the following steps: Step 1: Evenly mix the precursor, lithium salt and modifier, heat to a temperature T1 of 750°C to 850°C in an oxygen-containing atmosphere, and sinter for a sintering time of t1 to obtain a pre-lithiation intermediate, and quench the pre-lithiation intermediate in an environment with a temperature T2 of less than 10°C for a quenching time of t2 to obtain process sample A; Step 2: Place process sample A in an environment at temperature T3, disperse and spray the spheroidizing agent, and dry to obtain process sample B with the spheroidizing agent evenly coated on the surface; Step 3: In an oxygen-containing atmosphere, the process sample B is placed in an environment with a temperature T4 of 850°C to 1000°C for rapid calcination and crystallization. The calcination time is t3, and after cooling, a single crystal positive electrode material matrix C is obtained; Step 4: The single crystal positive electrode material substrate C is post-processed to obtain a high-fluidity lithium battery single crystal positive electrode material.

2. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1, characterized in that: In the step 1, the sintering time t1 is 1 h to 6 h, and the time t2 is 0.5 h to 2 h; the pre-lithiation intermediate in the step 1 is a partially disintegrated non-spherical agglomerate of primary particles, and the primary particles are small single crystal particles with a diameter of 1.5 to 2.5 μm.

3. A method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1 or 2, characterized in that: In the step 1, the precursor is at least one of an oxide, a hydroxide, a carbonate, and an organic acid salt containing effective elements, and the effective elements in the precursor are zero or one or more of nickel, cobalt, and Al, Mn, and Ti; the lithium salt is at least one of an oxide, a hydroxide, a carbonate, a phosphate, a nitrate, and an organic acid salt containing lithium; the modifier is at least one of an oxide, a halide, a carbonate, a hydroxide, a phosphide, a boride, and an organic compound containing effective elements, and the effective elements in the modifier are at least one of Al, Mn, Ti, Zr, Nb, Sr, W, B, Zn, Ta, Tl, Ga, V, Sn, Sb, Mo, Cs, Rb, Ru, In, and Ge.

4. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1 or 2, characterized in that: The temperature T3 in step 2 is -10°C to 200°C; the drying temperature is 100°C to 250°C, and the drying time is 1h to 20h.

5. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1 or 2, characterized in that: In the step 2, the spheroidizing agent is at least one of oxides, halides, carbonates, hydroxides, phosphides, borides, or organic compounds containing effective elements; the effective element in the spheroidizing agent is at least one of Mg, Si, Ca, Ba, Fe, Sc, Y, La, Ce, Na, and K.

6. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1 or 2, characterized in that: In the step 3, the calcination crystallization time t3 is 2h to 24h.

7. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1 or 2, characterized in that: The post-processing step in step 4 includes: the single crystal positive electrode material matrix C is crushed and gas-powdered, and then subjected to secondary coating and sintering or not, and then batch mixed, screened, demagnetized and then destaticized to obtain the single crystal positive electrode material matrix C.

8. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 7, characterized in that: The coating agent for the secondary coating is at least one of oxides, carbonates, hydroxides, phosphides, borides, halides, and organic compounds containing effective elements. The effective elements in the coating agent are at least one of Al, Mg, K, Ti, Nb, W, B, Mo, Si, Ca, Ba, C, and Fe. The secondary sintering temperature is 150° C. to 750° C., and the sintering time is 1 h to 20 h.

9. The method for preparing a high-fluidity lithium battery single crystal positive electrode material according to claim 1 or 2, characterized in that: The lithium element mole number of the lithium salt in the positive electrode material is 0.5-1.5, the effective element mole number of the precursor is 0.2-3.4, the effective element mole number of the modifier is 0.0005-0.005, the effective element mole number of the spheroidizer is 0.0005-0.005, and the effective element mole number of the coating agent is 0.0005-0.

004.

10. A high-fluidity lithium battery single crystal positive electrode material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9, the chemical formula of the positive electrode material is: Li 1+n Ni x Co y M z A m O 2+w , wherein, -0.5≤n≤0.5, 0.2≤x<1, 0≤y≤0.4, 0≤z≤2, 0≤m≤0.01, -0.5≤w≤2; M is zero, one or more of Al, Mn, and Ti; A is zero, one or more of Al, Mn, Mg, Ti, Fe, Zr, Y, Ca, Nb, Sr, Sc, W, B, Ba, Zn, Ce, Ta, Tl, Ga, La, V, Sn, Sb, Si, Mo, Cs, Rb, Ru, In, Ge, K, Na, C, H, F, Cl, and P; the repose angle of the high-fluidity lithium battery single crystal positive electrode material is less than 40°, and the particle size D50 is 2.0 to 6.5 μm.

Citation Information

Patent Citations

  • High-nickel positive electrode material and preparation method and application thereof

    CN111217408A

  • Preparation method of multistage porous single-crystal micron-sized LiMn2O4 positive electrode material

    CN114394624A

  • Positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery

    CN118039880A

  • Preparation method of LiFePO4 / C composite material doped with metal ions

    CN118529714A

  • Sagger and composition of sagger containing silicon carbide for manufacturing positive, negative electrode active material of secondary battery

    KR1020120102396A